Perceived Social Support among Nursing Collegian - Dr. Qahtan Q. Mohammed; Dr. Hassan A. Hussein (Zien Journals, 2022)
The study aims at assessing the students - instructor relationship within educational environment and evaluating the emotional perception toward relationship among nursing students and their instructors
Keywords: evaluating; relationship; nursing; instructors